Implementation of School Literacy on Students' Interest in Reading at State Elementary School 1 Paya Dapur Kluet Timur, South Aceh - Liani, Lisna; Yamin, M.; Soedirman, Soedirman (Elementary Education Research, 2024)
classes, from low to high grades, one of which is class IV in increasing students' interest in reading. This study aims to describe the implementation of school literacy at the habituation stage, the development stage and the learning stage in increasing students' interest in reading at Public Elementary School 1 Paya Dapur Kluet Timur, South Aceh. Qualitative research and descriptive research types. Class IV research subjects and the entire student population. data collection techniques using observation, interviews and documentation, and data analysis techniques by collecting data, presenting data and drawing conclusions. The first research results are the habituation stage, namely reading aloud or silently for 15 minutes. Do the 15-minute activity at the beginning, middle, or end of class. Write them in your diary. Second, the developmental stage is 15 minutes of reading before class. Respond to book enrichment activities during literacy class or activity time in the library or class reading corner or related lesson time. Various enrichment books. Third, the learning phase carried out at SDN Paya Dapur 1 is an enrichment book to study all subjects. Reading strategies are used to improve students' reading comprehension in all disciplines. According to students' literacy skills, carry out appropriate reading activities in oral, written, arts, crafts and other activities.